Relapse episodes in childhood primary nephrotic syndrome treated by alternate or three consecutive daily dose prednisone therapy - Denny Sujatno; M. P. Damanik; Purnomo Suryantoro (Indonesian Pediatric Society, 2008)
Background Prednison is still the drug of choice for the treatmentof nephrotic syndrome, especially for those with minimal change.Methods of treatment to optimize the effectiveness and efficacyare still in discussion.Objectives To evaluate the episode of relapsing minimal changenephrotic syndrome patients who received prednisone therapy byalternate or by three consecutive dose methods.Methods We performed a retrospective cohort study using medicalrecords of the patients with primary nephrotic syndrome admittedto Division of Nephrology, Sardjito Hospital, Yogyakarta fromJanuary 1995 to January 2005. Subjects were divided into twogroups, the first group treated with alternate days while thesecond group with three consecutive days prednisone program.Evaluation had been done to compare both treatment program(alternate days or consecutive days).Results Relapse episodes after six month recovery periods withalternate days treatment was 33% while those with consecutivedays was as high as 83% (P>O.Ol).Conclusion Alternate dose group has a lower relapse eventcompared to three consecutive dose group in children withnephrotic syndrome.